Pemanfaatan Instagram sebagai Media Komunikasi Pemasan Online Shop @Shoppingin_dong - Siti Hadarfiah; Satya Candrasari (UNIVERSITAS KALBIS, 2022)
Social media is not only used to connect and interact with other people, but also to communicate online marketing efforts by businesses. Instagram is one of the most popular social media platforms for marketing communications, and the @Shoppingin dong account is one of the users who use Instagram for marketing communication purposes. The purpose of this research is to find out more about how @Shoppingin dong, an online retailer using Instagram, conducts its marketing communications. This study collects data by means of observation, in-depth interviews, and documentation. @Shopping dong utilizes Instagram post photos, comments, captions, captions, hashtags, and business profiles for marketing communication purposes, as determined by data analysis.